The Queen's government - Jennings, Ivor, Sir, 1903-1965. (Harmondsworth: Penguin Books, 1954)
A full and authoritative account of the machinery of British democracy - the Monarchy, Parliament, the Cabinet, and the political and legal systems behind them.
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: United Kingdom -- Politics and government -- 20th century